'An entirely new land'? Italy's post-war culture and its Fascist past. Issue 1 (1st January 2016) - Leavitt, Charles L.
Abstract: Scholarship has for decades emphasized the significant continuities in Italian culture and society after Fascism, calling into question the rhetoric of post-war renewal. This article proposes a reassessment of that rhetoric through the analysis of five key metaphors with which Italian intellectuals represented national recovery after 1945: parenthesis, disease, flood, childhood and discovery. While the current critical consensus would lead us to expect a cultural conversation characterized by repression and evasion, an analysis of these five post-war metaphors instead reveals both a penetrating reassessment of Italian culture after Fascism and an earnest adherence to the cause of national revitalization. Foregrounding the inter-relation of Italy's prospects for change and its continuities with Fascism, these metaphors suggest that post-war Italian intellectuals conceived of their country's hopes for renewal, as well as its connections to the recent past, in terms that transcend the binary division favoured in many historical accounts.